Pathways to the Studies on Men and Masculinities in Bangladesh - Anisur Khan; Rasel Hussain; Md. Mizanur Rahman (HUMANISMA : Journal of Gender Studies, 2022)
In any society, the analysis of gender must include ‘men and masculinities’. But ‘men and masculinities’ as research attention is relatively underdeveloped in Bangladesh. This article provides an overview of the current studies on ‘men and masculinities’ in Bangladesh. Using Pub Med and Google Scholar databases, 37 closely relevant full-text documents were reviewed. This review uncovers that the ideal/hegemonic version of Bangladeshi masculinity is predominantly constructed/epitomized, amongst others, as being the provider, powerful, physically strong, good sexual performer, and having the ability to control wife. Across studies, the discourses, narratives, and practices of various masculinities in Bangladesh are expressed in the context of religion, migration, sexuality, fatherhood, suicide, violence, women empowerment, sports, and marginality. In some cases, the ideal/hegemonic version of Bangladeshi masculinity encounters serious tensions, ambiguities, resistances, and contestations. Alternative masculine discourses and narratives which reject and resist hegemonic masculine ideals and practices were also noted. This review ends with a call for a future research direction.